The Role Of Community Empowerment In Development At Marusu Sub-District Maros Regency - Sumandiyar, Adi; Nur, Hasruddin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This research aims to identify the factors that play a role in community empowerment in development at Marusu Subdistrict, Maros Regency. The research results show that factors that influence community participation in development in Marusu Subdistrict, Maros Regency are factors that originate from within the community itself, for example, the level of education, community income, and the community's self-awareness which is based on the religion that they adhere to. Apart from that, it is also caused by factors originating from the surrounding and outside environment of the community, including government leadership and their members or staffs (apparatus).